Création par la magie du verbe : genèse et développement du fantastique dans L’Eve future de Villiers de l’Isle-Adam - Miklós, Barbara (Verbum – Analecta Neolatina, 2012)
One of the most original personalities of 19th century French literature is Auguste de Villiers de l’Isle-Adam, whose literary works are almost completely unknown in Hungary, except for a few short stories translated in the last century. His novel L’Eve Future (The Future Eve), is a modern story of creation. This complex novel is atypical in many ways, and allows numerous analytical directions. This paper focuses on one possible reading of the text and examines the birth of the fantastic. The surnatural is present from the first lines of the text but in a masterfully structured way, it gradually, in an almost imperceptible way, takes control over the characters of the novel.